2016
DOI: 10.1111/medu.12971
|View full text |Cite
|
Sign up to set email alerts
|

Medical student satisfaction, coping and burnout in direct-entry versus graduate-entry programmes

Abstract: Our multi-institution data confirm that students are generally satisfied with their choice of entry pathway and do not confirm significant psychosocial benefits of graduate entry. Overall, our data suggest that direct-entry students cope with the workload and psychosocial challenges of medical school, in the first 2 years, as well as graduate-entry students. Burnout and alcohol use should be addressed in both pathways. Despite studies showing similar academic outcomes, and higher total costs, more programmes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Contrary to this, Castro-Sanchez et al [76] noted students' sudden abandonment of physical activities when finishing high school, as they are starting to be predominantly oriented to achievement of high academic performance. The case is not much different with the second year's university attendants, as coping with the workload and psychosocial challenges may be prolonged [77]. As if they assume that they will be more successful if they spend all their time and energy devoted to education [78] or are trying to please parents by "giving academic success priority over exercise" [79], university students of the first and second year gradually fall into a sedentary lifestyle by abruptly interrupting their previous physical engagement, which can result in reduction of their personal and academic efficiency.…”
Section: Sport Participation As a Factor Influencing Life Satisfactionmentioning
confidence: 99%
“…Contrary to this, Castro-Sanchez et al [76] noted students' sudden abandonment of physical activities when finishing high school, as they are starting to be predominantly oriented to achievement of high academic performance. The case is not much different with the second year's university attendants, as coping with the workload and psychosocial challenges may be prolonged [77]. As if they assume that they will be more successful if they spend all their time and energy devoted to education [78] or are trying to please parents by "giving academic success priority over exercise" [79], university students of the first and second year gradually fall into a sedentary lifestyle by abruptly interrupting their previous physical engagement, which can result in reduction of their personal and academic efficiency.…”
Section: Sport Participation As a Factor Influencing Life Satisfactionmentioning
confidence: 99%
“…In addition, certain personal characteristics such as being married (Robles et al, ; Brumpton et al, ; DeWitt et al, ) and difficulties in relationships (Zhang et al, ; Squires et al, ), have also been reported to heighten the sensitivity of students to stressful experiences. Moreover, research studies in the United States seem to indicate that females students, as compared to their male counterparts, appear to be more vulnerable to burnouts (Abeysekera and Dawson, ; Luthar, ; Yan et al, ; McLuckie et al, ).…”
Section: Challenges Of Present‐day Health Care Educationmentioning
confidence: 99%
“…While an increasing number of educational institutions currently offer counseling services (Tanaka et al, 2009;Archer, 2010;Mohr et al, 2011;Puertas et al, 2013;O'Mahony et al, 2016), most are ancillaries of other academic support services (Gliddon and Cridge, 2015;Brass et al, 2017;Eidson et al, 2018). Hence, a formal protocol for the specific assessment of the mental health of students should be established, as stresses in the early part of the program have been identified as powerful predictors of burnouts later in the program (Archer, 2010;Mohr et al, 2011;DeWitt et al, 2016;Fond et al, 2018). While numerous methods exist for detection of stress (reviewed by Bridges et al, 2016), the World Health Organization-Five Well-Being Index (WHO-5) questionnaire is particularly convenient (reviewed by Topp et al, 2015).…”
Section: Improve the Mental Health Of Studentsmentioning
confidence: 99%
“…The difference in male to female proportion influenced learning style preferences [15], empathy and stress levels [11,[17][18][19][20][21], and vulnerability to burnouts [6,22]. Being married also heightened the sensitivity of students to stressful experiences [23][24].…”
Section: Discussionmentioning
confidence: 99%